Financial Report Application Design: Case Study at Perhutani Tambak Ruyung East Pasir Jambu - Rima Melati; Alia Tri Utami; Asep Sudrajat; Cahyo Hermanto; Aris Dianto (Informatics Management, Engineering and Information System Journal, 2023)
Currently, PERUM Perhutani Tambak Ruyung Timur continues to rely on manual methods for financial reporting, resulting in incomplete financial reports. The process above has the potential to be significantly unproductive and inefficient, hence increasing the likelihood of errors in the recording procedure. Based on the backdrop above, PERUM Perhutani Tambak Ruyung Timur must implement a more pragmatic financial accounting recording system. Hence, the author interned at the organization above and produced a comprehensive Internship Report entitled "Designing a Financial Report Application: A Case Study at Perum Perhutani Tambak Ruyung Timur Pasir Jambu."The research method refers to the systematic approach researchers employ to investigate and gather data to answer research questions or test hypotheses.The research methodology employed in this study is the Descriptive Research Method. Object-Oriented Analysis and Design (OOAD) is employed in system development. The implementation of this system utilizes web programming languages, including PHP, CI, and UML. This research has yielded a financial reporting application software that is both effective and efficient.Based on the conducted research, it is inferred that the application developed by the researcher is anticipated to offer utility to PERUM Perhutani in streamlining the process of inputting financial data. Based on the acquired information, it is possible to fill incomplete financial reports by utilizing the programdeveloped by the researcher.